Gestão de cultura como reencantamento da sabedoria: uma proposta política de curadoria expandida - Monteiro, Rodrigo dos Santos (2022)
This is a thesis-exposition. A doctoral thesis that analyses but also experiences the curatorial exercise itself. The term curating presented here is not limited to a case study of an exhibition or festival, but it aims to show paths to foster sign flows, instead of managing structures that communicate consolidated assumptions. For this research, all cultural management is a gesture that interferes in cultural movements, to which the main component is the cognitive process (HUTCHINS, 1996). The central hypothesis is that the behaviors of artists and some other cultural networking professionals, such as curators and managers, have been guided by a logic that is not exclusively supported by the economic production, communication or the circulation flows, but also a logic that, contaminated by the values of the contemporary neoliberalism, produces in the body utilitarian ways of the perception, and the cognition – which, in turn, has an incisive impact on cognitive processes. The methodological approach is undisciplined, and articulates the Bodymedia Theory, by Katz and Greiner (2008, 2015); studies of the cognition made by Hutchins (1996), Varela (1995, 2017), and Damásio (2018); specific discussions on curating, raised by Obrist (2010, 2014), and Balzer (2012); aspects of the sociology of culture, discussed by Gielen (2010, 2015, 2018), and by Yúdice (2013); political philosophy from Dardot and Laval (2017), Agamben (2009, 2010, 2014, 2017), Virno (2013) and Lipovetsky and Serroy (2015); and some aspects of Peircean semiotics. As a methodology, we relate these bibliographic studies to practical experiences in cultural institutions, especially in art education and cultural production. Therefore, the goal is to propose an understanding of curating, management, and cultural politics that is not subservient to power relations consolidated by hierarchical dichotomies between nature and culture, body and mind, theory and practice, reason and emotion. The expected result is to collaborate with current debates, in order to demonstrate the urgency of thinking and creating managements, politics, and curating that destabilize usual parameters to reenact singular experiences of wisdom